Bilateral Fibroepithelial Polyps of The Lower Female Genital Tract With Atypical Stromal Cells (Pseudosarcoma Botryoides): A Case Reports - Demirtürk, Fazlı; Şener, Engin; Çalışkan, Ahmet Cantuğ; Aytan, Hakan (Gynecology Obstetrics & Reproductive Medicine, 2006)
A case of female genital tract f ibroepithelial polyps containing atypical stromal cells arising from the v ulva is described.Fibroepithelial stromal polyps of the vulv avaginal lesion are benign lesions that, when bland or hy pocellular, are readily recognized. The tumor was multipl and the highest one measured 4 centimeter in diameter. Cytologic atypia has been a previously recognized f eature in these lesions; howev er fibroepithelial polyps with stromal aty pia are an uncommon tumor of the v ulva, are rarely bilateral and combination of these f eatures has only rarely been documented. These tumors must be diff erentiated f rom sarcoma botry oides, which resemble both grossly and microscopically.